Synthesis, Crystal Structure and Characterization of [(CH3 CH2)4N] Mn1,5 Cl3 4H2O Cl 2(H2O) - Dhouib, Ikram; Guionneau, Philippe; Mhiri, Tahar; Elaoud, Zakaria (JOURNAL OF ADVANCES IN CHEMISTRY, 2012)
Single crystals of [(CH3CH2)4N] Mn1,5 Cl3 4H2O Cl 2(H2O) were grown by the slow evaporation technique and characterized by means of single-crystal X-ray diffraction, FT-IR and Raman spectroscopy. The title compound belongs to the triclinic space group PÂ with the following unit cell dimensions: a =7.5425(4) Ã…, b=9.8464 Ã…, c=13.7671(6) Ã…, Î±=89.951(3)Â°,Î²=89.753(3)Â°, Î³=81.861(3)Â°, Z=4. These structures have solved using direct methods and refined by least-squares analysis. The structure was solved by the direct method and refined to final R value of 0.0567. The projection of [(CH3CH2)4N] Mn1,5 Cl3 4H2O Cl 2(H2O) in the plan (a,b) shows an arrangement in layers perpendicular to the direction b . The structure consists of infinite parallel two-dimensional planes built connected ions and water molecules by strong O-Hâ€¦O and O-Hâ€¦Cl hydrogen bonding.